Work-break scheduling with real-time fatigue effect and recovery. Issue 3 (1st February 2020) - Li, Kai; Xu, Shuling; Fu, Hong
Abstract : In many situations, employees' performance decrements have generally been attributed to fatigue, and a flexibly designed work-break schedule can reduce their fatigue effect. This paper focuses upon the development and solution of model which minimises the actual completion time of all jobs, subject to a given fixed workload, through the selection of optimal work-break schedules. In this paper, several break periods are considered where each break activity is scheduled after a periodic time interval, and the employees' work rate first maintains a certain level and then declines during the work period. We propose a mathematical programming model and a heuristic algorithm to solve this problem. Our analysis finds that compared to the actual completion time of an employee without having a break, setting several reasonable fixed breaks makes work efficiency increased and improves employee satisfaction and reduces the makespan. Our findings light on the importance of understanding and setting break time in the work periods, and contribute to the improvement of employee satisfaction.